PENYELESAIAN KASUS WANPRESTASI PADA PEMBIAYAAN MURABAHAH DI BPRS DANA AMANAH SURAKARTA - Sachputri, Dyvia Nandhita; Wijaya, Ning Karna (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2021)
Abstract This research is based on the difference between the settlement of default in the Dana Amanah BPRS with the contents of the DSN-MUI No.47/DSN-MUI/II/2005. As in BPRS Dana Amanah does not release customer debt and settlement of default in murabahah financing does not use Basyarnas which is different from the provisions in the DSN-MUI Fatwa No. 47/DSN-MUI/II/2005. This research aims to describe and analyze how to resolve cases of default on murabahah financing at BPRS Dana Amanah and will be reviewed in terms of the DSN-MUI fatwa, namely the DSN-MUI Fatwa No. 47/DSN-MUI/II/2005 concerning settlement of murabahah receivables for unable to pay customers. This is to find out whether in practice the BPRS Dana Amanah has implemented the provisions of the Fatwa DSN-MUI No. 47/DSN- MUI/II/2005. The research methods in the preparation of this researchused qualitative field methods with data sources consisting of primary data and secondary data. Data collection techniques in this research were interviews and documentation. This research also uses data analysis techniques using qualitative data analysis. This results of this research is the settlement of default cases on murabahah financing is done in various ways, as administrative warning, disscusion with rescheduling, reconditioning, restructuring. mediation, sale of collateral / auction objects and finally the religious courts. This is not in accordance with the DSN-MUI Fatwa because from the review of the fatwa, dispute resolution / dispute is also resolved through the national sharia arbitration board (basyarnas) and if the customer is unable to pay, LKS shall release the debt. Keywords: Murabahah; Financing; Default.   Abstrak Penelitian ini didasarkan karena adanya perbedaan antara penyelesaian wanprestasi di BPRS Dana Amanah dengan isi Fatwa DSN-MUI No.47/DSN-MUI/II/2005. Sebagaimana di BPRS Dana Amanah tidak membebaskan utang nasabah dan Penyelesaian wanprestasi pada pembiayaan murabahah tidak menggunakan Basyarnas yang mana berbeda dengan ketentuan di Fatwa DSN MUI No. 47/DSN-MUI/II/2005. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis tentang cara penyelesaian kasus wanprestasi pada pembiayaan murabahah di BPRS Dana Amanah dan akan ditinjau dari segi fatwa DSN-MUI yaitu Fatwa DSN-MUI No. 47/DSN-MUI/II/2005 tentang Penyelesaian Piutang Murabahah Bagi Nasabah Tidak Mampu Membayar. Untuk mengetahui apakah dalam praktiknya BPRS Dana Amanah sudah menerapkan ketentuan dari Fatwa DSN- MUI No. 47/DSN-MUI/II/2005. Metode penelitian pada penyusunan penelitian ini menggunakan metode kualitatif lapangan dengan sumber data yang terdiri dari data primer dan data sekunder. Teknik pengumpulan data pada penelitian ini yaitu wawancara dan dokumentasi. Penelitian ini juga menggunakan teknik analisis data menggunakan analisis data kualitatif. Hasil penelitian ini yaitu penyelesaian kasus wanprestasi pada pembiayaan murabahah dilakukan dengan dengan berbagai cara. seperti peringatan administrasi, musyawarah melalui rescheduling, reconditioning, restructuring, mediasi, penjualan objek jaminan / pelelangan dan terakhir Putusan Pengadilan Agama. Hal ini kurang sesuai dengan Fatwa DSN-MUI karena apabila ditinjau dari fatwa tersebut penyelesaian perselisihan/sengketa diselesaikan juga melalui Badan Arbitrase Syariah Nasional (Basyarnas) dan apabila nasabah sudah tidak sanggup membayar maka LKS membebaskan utang tersebut. Kata Kunci: Murabahah; Pembiayaan; Wanprestasi.